RADIATION AND HYGIENIC MONITORING OF THE TERRITORIES OF KALUGA REGION AFFECTED DUE TO THE CHERNOBYL ACCIDENT - A. A. Kruchinin; A. A. Fadeev; L. I. Dichkovsky; D. V. Zolochevsky; T. A. Feoktistova (Радиационная гигиена, 2016)
The article contains radiation and hygienic evaluation of situation on the territories of Kaluga region, affected by the Chernobyl NPP accident immediately after the accident and in the present time. The results of radiation monitoring of environmental objects, food, drinking water as well as individual and collective exposure doses of population of affected territories and liquidators are presented. The set of measures aimed at the reduction of harmful affect of Chernobyl accident on the health of Kaluga region population is being proposed.